فعالية أدوات السياسة المالية على القطاع الصناعي في الجزائر - تامة, سمير; عثماني, حياة; خشيبة, الزهرة (جامعة الوادي - University of Eloued, 2021)
ملخص: تهدف الدراسة إلى إبراز مدى فعالية السياسة المالية في دعم القطاع الصناعي كأحد القطاعات المنتجة خارج المحروقات، حيث عمدت الدراسة إلى نمذجة وتحليلية لقياس أثر مؤشرات السياسة المالية ومعرفة مدى مساهمتها في دعم وتحفيز القطاع الصناعي في الجزائر خلال الفترة (1990-2017) وذلك باستخدام نموذج شعاع الانحدار الذاتيVAR ، أسفرت النتائج على أن السياسة المالية في الجزائر من خلال أداتي الإنفاق الحكومي والضرائب تكتسي فعالية في دعم القطاع الصناعي وتسهم في خلق قيمة مضافة صناعية، لكن حجم هذه الفعالية ليس بالمستوى المطلوب، إذ أن هذه الفعالية كانت ضئيلة نوعا ما وارتكزت على أداة دون أخرى. Abstract: The study aims to highlight the effectiveness of the financial policy in supporting the industrial sector as one of the productive sectors outside of hydrocarbons, as the study intended to model and analyze the effect of financial policy indicators and to know the extent of their contribution in supporting and stimulating the industrial sector in Algeria during the period (1990-2017), using the VAR self-regression beam model, the results showed that the fiscal policy in Algeria through the government spending and taxation tools is effective in supporting the industrial sector and contributing to creating industrial added value, but the size of this activity is not at the required level, as this effectiveness was somewhat small and was based on a tool without Other.
The effectiveness of fiscal policy instruments on Algeria's industrial sector A standard case study of Algeria using the VAR self-regression beam model for the period (1990-2017)
Keywords: الكلمات المفتاح : القيمة المضافة لقطاع الصناعة، الإنفاق الحكومي، الضرائب، VAR